Review of Strategies to Mitigate Dust Deposition on Solar Photovoltaic Systems - Gowtham Vedulla; Anbazhagan Geetha; Ramalingam Senthil (Energies, 2022)
In recent years, there has been an increased focus on developing and utilizing renewable energy resources due to several factors, including environmental concerns, rising fuel costs, and the limited supply of conventional fossil fuels. The most appealing green energy conversion technology is solar energy, and its efficient application can help the world achieve Sustainable Development Goal 7: Access to affordable, clean energy. Irradiance, latitude, longitude, tilt angle, and orientation are a few variables that affect the functioning of a solar photovoltaic (PV) system. Additionally, environmental factors like dust accumulation and soiling of panel surfaces impact the cost of maintaining and producing electricity from a PV system. Dust characteristics (kind, size, shape, and meteorological elements), one of the largest factors affecting PV panel performance, need to be investigated to devise specific solutions for efficiently harnessing solar energy. The essential findings of ongoing investigations on dust deposition on the surface of PV structures and various mitigating measures to tackle soiling issues are presented in this review study. This comprehensive assessment critically evaluates the current research on the soiling effect and PV system performance improvement techniques to determine the academic community’s future research priorities.